Personal Relationships : the Effect on Employee Attitudes, Behavior, and Well-being. - Eby, Lillian Turner de Tormes (Organizational frontiers series., 2012)
We know that positive, fulfilling and satisfying relationships are strong predictors of life satisfaction, psychological health, and physical well-being. This edited volume uses research and theory on the need to belong as a foundation to explore various types of relationships, with an emphasis on the influence of these relationships on employee attitudes, behaviors and well-being. The book considers a wide range of relationships that may affect work attitudes, specifically, supervisory, co-worker, team, customer and non-work relationships. The study of relationships spans many sub-areas wi.